Moving toward the Development and Effective Implementation of High-Quality Guidelines in Pediatric Surgery: A Review of the Literature - Irvine, Willemijn F.E.; Spivack, Olivia K.C.; Ista, Erwin (European Journal of Pediatric Surgery, 2024)
Applying evidence-based guidelines can enhance the quality of patient care. While robust guideline development methodology ensures credibility and validity, methodological variations can impact guideline quality. Besides methodological rigor, effective implementation is crucial for achieving improved health outcomes. This review provides an overview of recent literature pertaining to the development and implementation of guidelines in pediatric surgery. Literature was reviewed to provide an overview of sound guideline development methodologies and approaches to promote effective guideline implementation. Challenges specific to pediatric surgery were highlighted. A search was performed to identify published guidelines relevant to pediatric surgery from 2018 to June 2023, and their quality was collectively appraised using the AGREE II instrument. High-quality guideline development can be promoted by using methodologically sound tools such as the Guidelines 2.0 checklist, the GRADE system, and the AGREE II instrument. While implementation can be promoted during guideline development and post-publication, its effectiveness may be influenced by various factors. Challenges pertinent to pediatric surgery, such as limited evidence and difficulties with outcome selection and heterogeneity, may impact guideline quality and effective implementation. Fifteen guidelines were identified and collectively appraised as suboptimal, with a mean overall AGREE II score of 58%, with applicability being the lowest scoring domain. There are identified challenges and barriers to the development and effective implementation of high-quality guidelines in pediatric surgery. It is valuable to prioritize the identification of adapted, innovative methodological strategies and the use of implementation science to understand and achieve effective guideline implementation.
Keywords: guideline; methodology; quality; implementation; pediatric surgery